1991
DOI: 10.3354/meps070101
|View full text |Cite
|
Sign up to set email alerts
|

Testing the coral fragment size-dependent survivorship hypothesis for the calcareous hydrozoan Millepora complanata

Abstract: ABSTRACT. The distribution of living colonies of the calcareous hydrozoan Millepora complanata and broken and reattached millepore fragments was examined in m* quadrats along line transects on fringing reefs at Barbados, West Indies. Of the broken fragments 35 % reattached, but survival was not found to be size-dependent, in contrast to reports of breakage in Scleractinia. The number of reattached fragments was positively correlated with the total number of fragments and with the number of quadrats containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The seasonal growth assumption takes into account that species‐specific mean rates may covary as a result of unobserved seasonal factors (Appendix S1, Table S1). With or without fission size threshold . Fission rates were estimated in this study 19 months after transplantation, so rates may be specific to the range of observed colony sizes (consistent with observations that probability of fragmentation increases with colony size; Lewis ). Thus, thresholds (i.e.…”
Section: Methodssupporting
confidence: 85%
“…The seasonal growth assumption takes into account that species‐specific mean rates may covary as a result of unobserved seasonal factors (Appendix S1, Table S1). With or without fission size threshold . Fission rates were estimated in this study 19 months after transplantation, so rates may be specific to the range of observed colony sizes (consistent with observations that probability of fragmentation increases with colony size; Lewis ). Thus, thresholds (i.e.…”
Section: Methodssupporting
confidence: 85%
“…However, encrusting portions of colonies bear zooids (de Weerdt 1984) which were expanded. Transects were established perpendicular to the shore at 2 to 4 m depth, near the mid-reef crest where the hydrocoral is most abundant (Lewis 1991). Ten transects were marked out and the number of expanded and contracted colony branches recorded at different times during the morning and afternoon under a variety of prevailing sea and weather conditions during a period of about 1 mo.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have measured the importance of asexual propagation in coral communities (e.g. Tunnicliffe 1981, Lasker 1990, Lee & Noble 1990, Lewis 1991, Smith & Hughes 1999, have described the biological and ecological consequences of fragmentation upon colonies (e.g. Highsmith 1982, Lasker 1984, and have revealed specific mechanical strategies that enhance, and even control, fragmentation (e.g.…”
Section: Sexual and Asexual Propagation In Cupuladriid Bryozoansmentioning
confidence: 99%